El comportamiento de los estudiantes - Caiza Guerra, Cristina Elizabeth (2017)
The present research project: The behavior of the students during the Teaching-learning process in the children of the Sixth Year of the parallel "C" of General Basic Education of the Educational Unit "Victoria Vasconez Cuvi", the main objective was to determine Through a diagnostic investigation of how the behavior of the students of the sixth parallel year "C" in the teaching - learning process affects, through the bibliographical and field investigation to establish conclusions and recommendations, for which the problem was investigated Little treated through exploratory research, then the behavior in the context was described through descriptive research. The technical scientific basis of the research work is a bibliographical and Internet compilation of several authors focused on conceptually developing behavior, behavior, personality, discipline and the teaching-learning process. For the present investigation the hypothesis was raised: The behavior of the students improves the process of teaching learning in the children of the sixth year of Basic General Education of the Educational Unit already mentioned, the methodology used during the investigation of training were logical methods Or scientific and particular methods....